Perlindungan Hukum Bagi Dokter Oleh Rumah Sakit Dalam Menjalankan Praktik Kedokteran - Dedi Afandi; Uning Pratimaratri; Yofiza Media (Fakultas Kedokteran Universitas Riau, 2023)
Doctors practicing their profession are entitled to legal protection as stipulated in Article 50 of Law Number 29 of 2004 concerning Medical Practice. Hospitals must provide legal protection for doctors working in their hospitals by the hospital's obligations regulated in Article 29 paragraph (1) letter (s) of Law Number 44 of 2009 concerning Hospitals. In Indonesia, a statutory regulation has not explicitly regulated legal protection for doctors. This Literature Review discusses legal protection that hospitals can provide to doctors in practicing medicine. The form of preventive legal protection for doctors by hospitals is in the form of guarantees of legal protection, legal administration, authority for professional practice/clinical care, regulation of clinical practice, quality of medical services, provision of quality health service facilities and infrastructure and stipulation of prohibitions and sanctions. Forms of repressive legal protection for doctors by hospitals are handling complaints and claims, investigations, settlements, and financing of medical dispute cases. Legal certainty regarding the provision of legal protection must be included in the Hospital By-Laws. With legal certainty and regulations regarding legal protection, doctors will be protected and increase loyalty to hospitals.